Nutrition Impact Symptoms in Relation to Head and Neck Cancer Survivor’s Vegetable Intake and Use of Seasoning - Goon, Shatabdi; Pepino, M. Yanina; Arthur, Anna; Chapman-Novakofski, Karen (Asian Pacific Journal of Cancer Care, 2022)
Background: Most head and neck cancer (HNC) patients undergoing aggressive treatments with chemoradiotherapy and surgical resection of tumors suffer from symptoms long after treatment is completed that hinder adequate oral food intake, collectively known as Nutrition Impact Symptoms (NIS). Our aim was to examine the correlations between NIS and HNC survivors’ vegetable intake and use of seasoning. Methods: We conducted a 29-item telephone administrated survey to collect vegetable intake and seasoning habits among HNC survivors (n=22, age 61.4 ± 9.8 years, mean ± standard deviation) who received radiation therapy between 6 months and 10 years before recruitment identified through the cancer registry at Carle Foundation Hospital. Treatment-related side-effects (11 items) including difficulty swallowing, dry mouth, and mouth sores reflected NIS. A mean composite score was created for all the symptoms where higher scores indicated greater NIS. Spearman correlations examined the relationships between NIS, vegetable intake, and seasoning. Results: Half (50%) of the participants reported no change in their vegetable intake since diagnosis of cancer, and on average, ate 1 cup/day of total vegetables. Higher NIS scores associated with higher pumpkin and sweet potatoes intake (r (20) = .43, p<0.05), and there was a trend for higher scores of difficulties swallowing to be associated with lower corn and peas intake (r (20) =-.37, p=0.08). Participants with higher scores of problems with teeth and gums were less likely to use seasoning (r (20) = -.42, p<0.05). Conclusion: The findings support that HNC treatment can affect vegetable intake long after completion of radiotherapy. However, it would be premature for any recommendations to be derived from the present study for health professionals. A larger, observational study with a longer follow-up is therefore needed to examine these correlations.